The Great Indian Hornbill (Buceros bicornis) and Management of Old Growth forest Patches in Periyar Tiger Reserve - Harikumar, G.; Kaler, O. P.; Joseph, Sherly; Peeyuskutty, K. J.; Zacharias, V. J. (Indian Forester, 2001)
The Great Indian Hornbill is now an endangered species although in Protected Areas it is fairly common. Systematic studies have not been conducted through stray notes are available. A status survey was conducted in Periyar Tiger Reserve. It has shown its wide distribution in evergreen and semi-evergreen forests where it is found singly or in groups. It prefers old growth forest patches. Nesting take place from February to May which is related to fruiting season are figs. Nesting is done on tall old trees. Young ones are fed on figs and occasionally Lizards and even Snakes. Entrances are vertical to circular, the height of nests being 8 to 25 m from the ground. Photography is posing a management problem and in some cases the birds did not return to the nest which they generally did when they were not disturbed.